Un cortège « hors des cadres » au devant de la manifestation des organisations syndicales - Hugo Melchior (Cahiers d’histoire.)
Since spring 2016, union organizations, as much as police forces charged with the control and surveillance of the masses of protesters, are being confronted regularly, whether it is in Paris and in other cities around the country, to a congregation of actors which, beyond its social and political heterogeneity, forms in front of the protest what as been designated and popularized by its founders under the name of the “head of the cortège” (“cortège de tête”). The stakes of this article are to make intelligible this wrongly identified object which intrigues, but also to realize the way union officials position themselves in front of this invasive and unruly collective actor, which deeply disturbs the protest order.